PENGARUH KOMUNIKASI ORGANISASI, KEPEMIMPINAN TRANSFORMASIONAL DAN KEADILAN ORGANISASI TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR SERTA DAMPAKNYA PADA KINERJA DAN KOMITMEN ORGANISASIONAL - Triyanthi, Meylinda Tr; Subudi, Made (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2018)
This purpose research aims to analyze and explain the influence of organizational communication, transformational leadership, and organizational citizenship toward Organizational Behavior (OCB), and how Organizational Citizenship Behavior (OCB) has an effect on the performance and organizational commitment of PT. Yamaha Direct Distribution Sales Bali. The population of this research is all permanent employees who work in PT. Yamaha Direct Distribution Sales Bali as many as 37 people. Sample determination technique used in this research is saturated or census sampling with research instrument using questionnaire. Data were analyzed using SEM (Structural Equation Modeling) analysis based on component or variance that is PLS (Partial Least Square). The results showed that organizational communication, transformational leadership, and organizational justice had a positive and significant effect on Organizational Citizenship Behavior. Organizational Citizenship Behavior has a positive and significant impact on employee performance, and Organizational Citizenship Behavior has a positive and significant effect on organizational commitment of employees.